Avaliação da relação do índice tornozelo-braquial com a gravidade da doença arterial coronária - Petracco, Andrea Mabilde (2017)
Introduction: Peripheral Artery Disease (PAD) is associated with cardiovascular events and can be diagnosed and estimated through the Ankle-Brachial Index (ABI). It is well established that ABI is an aggravating factor in the stratification of cardiovascular risk, but its contribution to defining the severity of coronary artery disease is not well established. Objective: The study compared the value of ABI with the severity of coronary atherosclerotic disease by the Syntax (ES) Score in patients with Acute Coronary Syndrome (ACS). Methods: A prospective study with the ABI measurement of all patients hospitalized with ACS at the São Lucas Hospital of PUCRS, consecutively, from May to September 2016, and the comparison of their value with ES of these patients and the respective forms of presentation of ACS. Results: We studied101 patients, mean age 62.6 ± 12 years, 58 (57.4%) males, 74 (82.2%) hypertensive, 33 (45.8%) diabetics and 46 (45.5%) presented acute myocardial infarction with ST segment depression (STEMI) . The frequency of PAD was 3 times higher than that described in the general population. The severity of PAD was not related to the anatomical severity of the coronary disease. We found a significant association of patients with intermediate ES with non-ST elevation myocardial infarction (STEMI) and low ES with unstable angina (UA) (P = 0.015), who remained even after adjusting for age, smoking, family history of CAD and prior CAD. OR (95% CI-1.02-1.25). Conclusions: Our results demonstrate that patients with ABI lower than 0.9 were not associated with a greater complexity of coronary atherosclerotic disease, as determined by ES in patients with ACS. Patients with NSTEMI were more associated with intermediate ES.